The Design and Implementation of Criterion- Referenced Assessment in a First Year Undergraduate Core Law Unit - Kelley Burton; Natalie Cuffe (Legal Education Review)
This issue of the Legal Education Review has involved the efforts of many people, mainly academics, who have volunteered their time and expertise with little thought of reward or recognition. Special thanks needs to go to the Faculty of Law at UTS and Professor Michael Adams for the support provided through the ALTA office.